Flipping an English writing class with technology-enhanced just-in-time teaching and peer instruction - Zou, Di; Xie, Haoran (Interactive learning environments, 2019)
Just-in-time teaching and peer instruction are two student-centred approaches that have been widely employed in various science subjects but seldom in language classrooms. This research proposed a flipped learning model through technology-enhanced just-in-time teaching and peer instruction and investigated the effectiveness of this model in promoting English learning. Two groups of upper intermediate EFL learners participated in the study and learned in two different flipped learning modes, one with the newly proposed approach and the other with the conventional flipped learning approach. The results showed that the proposed model outperformed the conventional model in promoting the development of students' writing skills, motivation, and tendency of critical thinking. The use of an assessment-centred tool (e.g. EDpuzzle) for interactive videos and cloud-based tools for real-time collaboration (e.g. Padlet and Google Docs) assisted in creating scaffolded learning experience, sharing culture, and opportunities of peer instruction for students in the flipped classroom with Just-in-time teaching and peer instruction. Such results implied that our flipped learning model is very conducive to language learning, and it is advised to be employed more widely in various language learning classes.